2019
DOI: 10.3390/mi11010013
|View full text |Cite
|
Sign up to set email alerts
|

Direct Patterning and Spontaneous Self-Assembly of Graphene Oxide via Electrohydrodynamic Jet Printing for Energy Storage and Sensing

Abstract: The macroscopic assembly of two-dimensional materials into a laminar structure has received considerable attention because it improves both the mechanical and chemical properties of the original materials. However, conventional manufacturing methods have certain limitations in that they require a high temperature process, use toxic solvents, and are considerably time consuming. Here, we present a new system for the self-assembly of layer-by-layer (LBL) graphene oxide (GO) via an electrohydrodynamic (EHD) jet p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…When the jetting speed is higher than the moving speed of the X-Y stage (or needle), wavy filaments are produced [80]. Previous studies found the line width of EHD filament decreased with the increase of the moving speed of the X-Y stage (or needle) [92,98], while He et al gave the opposite result [99]. That is because they used different solutions and parameters to conduct experiments.…”
Section: Process Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…When the jetting speed is higher than the moving speed of the X-Y stage (or needle), wavy filaments are produced [80]. Previous studies found the line width of EHD filament decreased with the increase of the moving speed of the X-Y stage (or needle) [92,98], while He et al gave the opposite result [99]. That is because they used different solutions and parameters to conduct experiments.…”
Section: Process Parametersmentioning
confidence: 99%
“…Furthermore, the change of voltage value may enlarge or diminish the diameter of outputs based on different ink formulas. Zhang et al found the size of obtained outputs decreased with the increase of applied high voltage when fabricating graphene oxide for energy storage and sensing via EHD printing [92]. Moghadam et al indicated the obtained beads diameter slightly increased with the increase of applied voltage beyond a certain value [93].…”
Section: Process Parametersmentioning
confidence: 99%
“…Other nanoparticles aligned by EHD include the stainless steel particles and rods, [230] micronano aluminum particles, [231] quantum dots, [232] Janus particles, [233] CNTs, [234] graphene, [235] graphene oxide (GO). [236] The EHD method showed the ability to assemble nano particles with regular patterns and the control of polymer mor phologies. Rogers and coworkers demonstrated the use of EHD to pattern large areas with block copolymers of (PScoMMA) with various molecular weights and compositions.…”
Section: Ehd Jet-induced Alignmentmentioning
confidence: 99%
“…Numerous other EHD jet-printed electrode materials have been presented in the literature. 40,51,53,90,[94][95][96][97][98][99][100][101][102]…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%